The Value Relevance of Corporate Social Disclosures and the Role of Good Corporate Governance: Evidence in Indonesia - Purwant, Dyah; Nurhidayati, Nurhidayati (International Journal of Engineering and Technology, 2018)
Our study aims to investigate the value relevance of corporate social disclosures (CSD) and the role of good corporate governance. For fulfilling the objectives, we analyze the CSD’s content of firm listed on the Indonesian stock exchange during 2013-2016, and used descriptive and regression analysis. The content analysis revealed that each type of industry has a different broad of social disclosure. Each of firm focuses on disclosing social responsibilities according to its characteristics of business activities, which also the responsibilities are regulated by government.  Based on these preliminary findings, we examine whether the value relevance of each aspect of CSD differ. We document empirical findings to current debate on the relationship between environmental disclosure and shareholder value. The result is CSD has value relevance, either to the firm’s value and its financial performance. Another finding is each of CSD’s aspect has different of value relevance. The most disclosing aspect is labor-related. The firm with wider disclosure on labor-related has higher firm value and better future financial performance. Another finding is good corporate governance has a role to strengthen the relevance of CSD. The presence of foreign commissioners positively influences the value of the firm, as well as audit committees and majority ownership and managerial ownership.